2020
DOI: 10.1212/wnl.0000000000009093
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian diet and incidence of total, ischemic, and hemorrhagic stroke in 2 cohorts in Taiwan

Abstract: ObjectiveTo determine how a vegetarian diet affects stroke incidence in 2 prospective cohorts and to explore whether the association is modified by dietary vitamin B12 intake.MethodsParticipants without stroke in the Tzu Chi Health Study (cohort 1, n = 5,050, recruited in 2007–2009) and the Tzu Chi Vegetarian Study (cohort 2, n = 8,302, recruited in 2005) were followed until the end of 2014. Diet was assessed through food frequency questionnaires in both cohorts at baseline. Stroke events and baseline comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 47 publications
1
57
0
Order By: Relevance
“…Interestingly, the preventive effect of exercise and cultural activities on cognition is enhanced when conducted in company, reinforcing the importance of social networks [ 147 ]. Furthermore, Mediterranean diet is generally recommended to reduce the risk of cognitive decline [ 148 , 149 ], and both Mediterranean and vegetarian diets were shown to be associated with stroke risk reduction [ 150 , 151 ▪ ].…”
Section: Management Of Vascular Cognitive Impairmentmentioning
confidence: 99%
“…Interestingly, the preventive effect of exercise and cultural activities on cognition is enhanced when conducted in company, reinforcing the importance of social networks [ 147 ]. Furthermore, Mediterranean diet is generally recommended to reduce the risk of cognitive decline [ 148 , 149 ], and both Mediterranean and vegetarian diets were shown to be associated with stroke risk reduction [ 150 , 151 ▪ ].…”
Section: Management Of Vascular Cognitive Impairmentmentioning
confidence: 99%
“…The results in this study are more in line with the EPIC-Oxford Cohort, which found a 26% reduced risk of cataracts in vegetarians compared with nonvegetarians, 20 than with the positive cross-sectional association found for Asians in Leicester. 21 Despite lower vitamin B-12 status and its corresponding elevation of homocysteine in vegetarians in both this cohort 26 and the EPIC Oxford cohort, 27 vegetarian and vegan diets were associated with protective rather than harmful association. These findings contrast that of the Blue Mountains Eye Study, in which both serum homocysteine elevation and methylenetetrahydrofolate reductase C677T polymorphism (CT/TT vs CC-polymorphisms that influence homocysteine level) were associated with a higher risk of cortical cataracts.…”
Section: Discussionmentioning
confidence: 76%
“…19 The findings from this current study suggest that the potential benefits of vegetarian diets might outweigh the risk related to homocysteine. Unfortunately, in both the EPIC-Oxford and this current study, only a limited number of participants had plasma homocysteine available, 26,27 precluding further analysis on how homocysteine might influence cataract risk in vegetarians. Vegetarian diets are defined by meat avoidance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, after McEvoy et al first presented the relationship between Hcy and hemorrhagic stroke [ 16 ], its role in hemorrhagic stroke subsequently reported remains controversial [ 17 19 ], let alone in bAVMs. Currently, most studies, including meta-analyses, failed to confirm this association [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%